Maria Joaquina de Almeida: fazendeira de café no vale do Paraíba - Almeida, Diego Amaro de (2014)
The present essay is concerned with the quotidian of Maria Joaquina de Almeida, widow and farmer in Vale do Paraíba Paulista, in the 19th century, golden age of coffe established brasilian economy. We try to consider over the widow s social universe, trying to verify over the relationship between the things of the female world and the male world. In this context, we investigate how the exigences of the cofee business and the great fortune inherited, implyed a competent administration, a careful slaves management, and unusual social relationships for a woman in those times. We try to identify characteristics of the profile of the woman in those times to infer over the gender conflitcs that permeates the specific social world of Brazil History. This searching was from a theoretical approaches, the lectures of inventories and books of charges token as primary source documents, besides memorialists records. This complex whole permitted a greater understanding of the social universe of Maria Joaquina de Almeida, characterised by social issues where the places of the genders was ordered by solid patterns and, in principle, invariables